The emerging significance of furan fatty acids in food, nutrition, and potential therapeutic use - Fei Chang; Pascal Rowart; Sonia R. Salvatore; Oren Rom; Mark Mascal; Francisco J. Schopfer (Food Chemistry, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Development of a Detailed Finite Element Model of the BIPED MK2 and Verification of Fidelity in Two Cases of Blunt Impact - Robert Chauvet; Ashton Martin; Jennifer Rovt; Oren Petel; Simon Ouellet; Lindsey Westover; Christopher R. Dennison (Annals of Biomedical Engineering, 2025)

A prospective ecological momentary assessment study of an ayahuasca retreat: exploring the salutary impact of acute psychedelic experiences on subacute affect and mindfulness skills in daily life - Sharon R. Sznitman; Yoel A. Behar; Sheila Daniela Dicker-Oren; Tamar Shochat; David Meiri; Nader Butto; David Roe; Amit Bernstein (Psychopharmacology, 2025)
Rationale To examine the acute effects of ayahuasca use and their relationship to sub-acute changes in affect and mindfulness in a non-clinical sample, addressing the need for a better understanding of ayahuasca’s immediate and short-term impacts as interest in its use grows. Objectives Using prospective ecological assessment, this study investigates how ayahuasca used at a 4-day retreat affects positive/negative affect and mindfulness skills in daily living compared to pre-retreat. Additionally, we explore acute psychedelic experiences during the ayahuasca retreat, assessed retrospectively 1–2 days post-retreat, as potential mechanisms for theorized effects in daily living post-retreat. Methods Thirty-six participants reported positive/negative affect and mindfulness skills three times daily for 5 days before and after the retreat. Baseline assessments included lifetime psychedelic experience, and post-retreat assessments covered acute ayahuasca experiences. Mixed-effect linear models were used to analyze the data. Results Post-retreat, we observed reduced negative affect, increased positive affect, and enhanced mindfulness skills in daily living. Ayahuasca-induced acute experiences, such as time/space transcendence, emotional breakthrough and challenging experiences predicted greater subacute positive affect. Notably, none of these experiences were linked to subacute improvements in negative affect or mindfulness. No participants showed clinically significant adverse responses post-retreat, and only 5.5% exhibited some degree of potentially clinically significant deterioration in affect. Conclusions Ayahuasca use may lead to improvement in mood and mindfulness skills, and key acute psychedelic experiences induced by ayahuasca may be important to some of these salutary effects, positive affect in particular.

Increased leaf area index and efficiency drive enhanced production under elevated atmospheric [ CO 2 ] in a pine‐dominated stand showing no progressive nitrogen limitation - S. Palmroth; D. Kim; C. A. Maier; D. Medvigy; A. P. Walker; R. Oren (Global Change Biology, 2024)
Enhancement of net primary production (NPP) in forests as atmospheric [CO 2 ] increases is likely limited by the availability of other growth resources. The Duke Free Air CO 2 Enrichment (FACE) experiment was located on a moderate‐fertility site in the southeastern US, in a loblolly pine ( Pinus taeda L.) plantation with broadleaved species growing mostly in mid‐canopy and understory. Duke FACE ran from 1994 to 2010 and combined elevated [CO 2 ] (eCO 2 ) with nitrogen (N) additions. We assessed the spatial and temporal variation of NPP response using a dataset that includes previously unpublished data from 6 years of the replicated CO 2 × N experiment and extends to 2 years beyond the termination of enrichment. Averaged over time (1997–2010), NPP of pine and broadleaved species were 38% and 52% higher under eCO 2 compared to ambient conditions. Furthermore, there was no evidence of a decline in enhancement over time in any plot regardless of its native site quality. The relation between spatial variation in the response and native site quality was suggested but inconclusive. Nitrogen amendments under eCO 2 , in turn, resulted in an additional 11% increase in pine NPP. For pine, the eCO 2 ‐induced increase in NPP was similar above‐ and belowground and was driven by both increased leaf area index ( L ) and production efficiency (PE = NPP/ L ). For broadleaved species, coarse‐root biomass production was more than 200% higher under eCO 2 and accounted for the entire production response, driven by increased PE. Notably, the fraction of annual NPP retained in total living biomass was higher under eCO 2 , reflecting a slight shift in allocation fraction to woody mass and a lower mortality rate. Our findings also imply that tree growth may not have been only N‐limited, but perhaps constrained by the availability of other nutrients. The observed sustained NPP enhancement, even without N‐additions, demonstrates no progressive N limitation.

Urbanization comprehensively impairs biological rhythms in coral holobionts - Yaeli Rosenberg; Noa Simon‐Blecher; Maya Lalzar; Ruth Yam; Aldo Shemesh; Shahar Alon; Gabriela Perna; Anny Cárdenas; Christian R. Voolstra; David J. Miller; Oren Levy (Global Change Biology, 2022)
Coral reefs are in global decline due to climate change and anthropogenic influences (Hughes et al., Conservation Biology , 27: 261–269, 2013). Near coastal cities or other densely populated areas, coral reefs face a range of additional challenges. While considerable progress has been made in understanding coral responses to acute individual stressors (Dominoni et al., Nature Ecology & Evolution , 4: 502–511, 2020), the impacts of chronic exposure to varying combinations of sensory pollutants are largely unknown. To investigate the impacts of urban proximity on corals, we conducted a year‐long in‐natura study—incorporating sampling at diel, monthly, and seasonal time points—in which we compared corals from an urban area to corals from a proximal non‐urban area. Here we reveal that despite appearing relatively healthy, natural biorhythms and environmental sensory systems were extensively disturbed in corals from the urban environment. Transcriptomic data indicated poor symbiont performance, disturbance to gametogenic cycles, and loss or shifted seasonality of vital biological processes. Altered seasonality patterns were also observed in the microbiomes of the urban coral population, signifying the impact of urbanization on the holobiont, rather than the coral host alone. These results should raise alarm regarding the largely unknown long‐term impacts of sensory pollution on the resilience and survival of coral reefs close to coastal communities.

“Nobody Is Talking About It”: Diné (Navajo) Communities Speak About Stomach Cancer and Helicobacter pylori Infections - Carmenlita Chief; Priscilla R. Sanderson; Angela A. A. Willeto; Alfred Yazzie; Alexis McKinley; Fernando P. Monroy; Robin B. Harris; Eyal Oren (Journal of Cancer Education, 2022)

The response of coarse root biomass to long‐term CO 2 enrichment and nitrogen application in a maturing Pinus taeda stand with a large broadleaved component - Chris A. Maier; Kurt H. Johnsen; Pete H. Anderson; Sari Palmroth; Dohyoung Kim; Heather R. McCarthy; Ram Oren (Global Change Biology, 2022)
Elevated atmospheric CO 2 (eCO 2 ) typically increases aboveground growth in both growth chamber and free‐air carbon enrichment (FACE) studies. Here we report on the impacts of eCO 2 and nitrogen amendment on coarse root biomass and net primary productivity (NPP) at the Duke FACE study, where half of the eight plots in a 30‐year‐old loblolly pine ( Pinus taeda , L.) plantation, including competing naturally regenerated broadleaved species, were subjected to eCO 2 (ambient, aCO 2 plus 200 ppm) for 15–17 years, combined with annual nitrogen amendments (11.2 g N m −2 ) for 6 years. Allometric equations were developed following harvest to estimate coarse root (>2 mm diameter) biomass. Pine root biomass under eCO 2 increased 32%, 1.80 kg m −2 above the 5.66 kg m −2 observed in aCO 2 , largely accumulating in the top 30 cm of soil. In contrast, eCO 2 increased broadleaved root biomass more than twofold (aCO 2 : 0.81, eCO 2 : 2.07 kg m −2 ), primarily accumulating in the 30–60 cm soil depth. Combined, pine and broadleaved root biomass increased 3.08 kg m −2 over aCO 2 of 6.46 kg m −2 , a 48% increase. Elevated CO 2 did not increase pine root:shoot ratio (average 0.24) but increased the ratio from 0.57 to 1.12 in broadleaved species. Averaged over the study (1997–2010), eCO 2 increased pine, broadleaved and total coarse root NPP by 49%, 373% and 86% respectively. Nitrogen amendment had smaller effects on any component, singly or interacting with eCO 2 . A sustained increase in root NPP under eCO 2 over the study period indicates that soil nutrients were sufficient to maintain root growth response to eCO 2 . These responses must be considered in computing coarse root carbon sequestration of the extensive southern pine and similar forests, and in modelling the responses of coarse root biomass of pine–broadleaved forests to CO 2 concentration over a range of soil N availability.

Endosymbiont Communities in Pachyseris speciosa Highlight Geographical and Methodological Variations - Sudhanshi S. Jain; Lutfi Afiq-Rosli; Bar Feldman; Ismael Kunning; Oren Levy; Ralph R. Mana; Benjamin J. Wainwright; Danwei Huang (Frontiers in Marine Science, 2021)
Reef-building corals live in symbiosis with the phototrophic dinoflagellate family Symbiodiniaceae, which comprises diverse genera such as Cladocopium and Durusdinium . Pachyseris speciosa , a widely distributed Indo-Pacific coral found in a variety of reef habitats, is known to be associated with these two Symbiodiniaceae genera, but little is known about the biogeographic variability of the endosymbiont communities across the region. In this study, the diversity and dominance patterns of Symbiodiniaceae at the western and eastern areas of the Central Indo-Pacific region were examined. We sampled Pachyseris speciosa colonies at seven and six sites in Singapore and Papua New Guinea, respectively, and genotyped their endosymbionts based on the internal transcribed spacer (ITS) markers using two distinct methods, quantitative polymerase chain reaction (qPCR) and high-throughput sequencing (HTS). Results showed 92% of all colonies in Singapore exhibiting Cladocopium dominance. There was a higher abundance of Durusdinium compared to Cladocopium in certain colonies from one site, Pulau Hantu (mean Durusdinium abundance of 90%, compared to 0–14% among all other sites). In contrast, variation in the endosymbiont communities was generally higher among sites in Papua New Guinea. Cladocopium expectedly dominated most colonies (75%), although colonies from Kimbe Bay (85%) and Kavieng (65%) showed Durusdinium dominance. Between localities, relative genus abundances based on qPCR were not significantly different, but HTS showed that the ratio of Durusdinium over Cladocopium was significantly higher in Papua New Guinea corals. Notably, 6% of colonies from Singapore and 15% from Papua New Guinea showed endosymbiont dominance patterns that were inconsistent between the two methods, underscoring the need for further validation of symbiotic algal quantification based on HTS. The richness of ITS2 type profiles was clearly lower among colonies from the impacted and turbid reefs of Singapore compared to the less urbanized reefs of Papua New Guinea. These coral intraspecific variations of Symbiodiniaceae communities within and among localities suggest that local conditions are important drivers of endosymbiosis and may ultimately influence corals’ resilience against global stressors such as ocean warming.

Evapotranspiration and water yield of a pine‐broadleaf forest are not altered by long‐term atmospheric [CO 2 ] enrichment under native or enhanced soil fertility - Eric J. Ward; Ram Oren; Hyun Seok Kim; Dohyoung Kim; Pantana Tor‐ngern; Brent E. Ewers; Heather R. McCarthy; Andrew Christopher Oishi; Diane E. Pataki; Sari Palmroth; Nathan G. Phillips; Karina V. R. Schäfer (Global Change Biology, 2018)
Changes in evapotranspiration ( ET ) from terrestrial ecosystems affect their water yield ( WY ), with considerable ecological and economic consequences. Increases in surface runoff observed over the past century have been attributed to increasing atmospheric CO 2 concentrations resulting in reduced ET by terrestrial ecosystems. Here, we evaluate the water balance of a Pinus taeda (L.) forest with a broadleaf component that was exposed to atmospheric [CO 2 ] enrichment (ECO 2 ; +200 ppm) for over 17 years and fertilization for 6 years, monitored with hundreds of environmental and sap flux sensors on a half‐hourly basis. These measurements were synthesized using a one‐dimensional Richard's equation model to evaluate treatment differences in transpiration ( T ), evaporation ( E ), ET , and WY . We found that ECO 2 did not create significant differences in stand T, ET , or WY under either native or enhanced soil fertility, despite a 20% and 13% increase in leaf area index, respectively. While T , ET , and WY responded to fertilization, this response was weak ( E responded to ECO 2 in the first 7 years of the study, this effect was of negligible magnitude ( P. taeda , our results imply that recent observations of increased global streamflow cannot be attributed to decreases in ET across all ecosystems, demonstrating a great need for model–data synthesis activities to incorporate our current understanding of terrestrial vegetation in global water cycle models.

Dynamics of soil CO 2 efflux under varying atmospheric CO 2 concentrations reveal dominance of slow processes - Dohyoung Kim; Ram Oren; James S. Clark; Sari Palmroth; A. Christopher Oishi; Heather R. McCarthy; Chris A. Maier; Kurt Johnsen (Global Change Biology, 2017)
We evaluated the effect on soil CO 2 efflux ( F CO 2 ) of sudden changes in photosynthetic rates by altering CO 2 concentration in plots subjected to +200 ppmv for 15 years. Five‐day intervals of exposure to elevated CO 2 ( eCO 2 ) ranging 1.0–1.8 times ambient did not affect F CO 2 . F CO 2 did not decrease until 4 months after termination of the long‐term eCO 2 treatment, longer than the 10 days observed for decrease of F CO 2 after experimental blocking of C flow to belowground, but shorter than the ~13 months it took for increase of F CO 2 following the initiation of eCO 2 . The reduction of F CO 2 upon termination of enrichment (~35%) cannot be explained by the reduction of leaf area (~15%) and associated carbohydrate production and allocation, suggesting a disproportionate contraction of the belowground ecosystem components; this was consistent with the reductions in base respiration and F CO 2 ‐temperature sensitivity. These asymmetric responses pose a tractable challenge to process‐based models attempting to isolate the effect of individual processes on F CO2 .

A typology of fisheries management tools: using experience to catalyse greater success - Elizabeth R Selig; Kristin M Kleisner; Oren Ahoobim; Freddy Arocha; Annabelle Cruz‐Trinidad; Rod Fujita; Mafaniso Hara; Laure Katz; Patrick McConney; Blake D Ratner; Lina M Saavedra‐Díaz; Anne‐Maree Schwarz; et al. (Fish and Fisheries, 2017)
Fisheries provide nutrition and livelihoods for coastal populations, but many fisheries are fully or over‐exploited and we lack an approach for analysing which factors affect management tool performance. We conducted a literature review of 390 studies to assess how fisheries characteristics affected management tool performance across both small‐scale and large‐scale fisheries. We defined success as increased or maintained abundance or biomass, reductions in fishing mortality or improvements in population status. Because the literature only covered a narrow set of biological factors, we also conducted an expert elicitation to create a typology of broader fishery characteristics, enabling conditions and design considerations that affect performance. The literature suggested that the most commonly used management tool in a region was often the most successful, although the scale of success varied. Management tools were more often deemed successful when used in combination, particularly pairings of tools that controlled fishing mortality or effort with spatial management. Examples of successful combinations were the use of catch limits with quotas and limited entry, and marine protected areas with effort restrictions. The most common factors associated with inadequate biological performance were ‘structural’ issues, including poor design or implementation. The expert‐derived typologies revealed strong local leadership, high community involvement and governance capacity as common factors of success across management tool categories (i.e. input, output and technical measures), but the degree of importance varied. Our results are designed to inform selection of appropriate management tools based on empirical data and experience to increase the likelihood of successful fisheries management.

Analysis of the bacteriorhodopsin-producing haloarchaea reveals a core community that is stable over time in the salt crystallizers of Eilat, Israel - Nikhil Ram-Mohan; Aharon Oren; R. Thane Papke (Extremophiles, 2016)

Sustained effects of atmospheric [ CO 2 ] and nitrogen availability on forest soil CO 2 efflux - A. Christopher Oishi; Sari Palmroth; Kurt H. Johnsen; Heather R. McCarthy; Ram Oren (Global Change Biology, 2014)
Soil CO 2 efflux ( F soil ) is the largest source of carbon from forests and reflects primary productivity as well as how carbon is allocated within forest ecosystems. Through early stages of stand development, both elevated [ CO 2 ] and availability of soil nitrogen (N; sum of mineralization, deposition, and fixation) have been shown to increase gross primary productivity, but the long‐term effects of these factors on F soil are less clear. Expanding on previous studies at the Duke Free‐Air CO 2 Enrichment ( FACE ) site, we quantified the effects of elevated [ CO 2 ] and N fertilization on F soil using daily measurements from automated chambers over 10 years. Consistent with previous results, compared to ambient unfertilized plots, annual F soil increased under elevated [ CO 2 ] (ca. 17%) and decreased with N (ca. 21%). N fertilization under elevated [ CO 2 ] reduced F soil to values similar to untreated plots. Over the study period, base respiration rates increased with leaf productivity, but declined after productivity saturated. Despite treatment‐induced differences in aboveground biomass, soil temperature and water content were similar among treatments. Interannually, low soil water content decreased annual F soil from potential values – estimated based on temperature alone assuming nonlimiting soil water content – by ca. 0.7% per 1.0% reduction in relative extractable water. This effect was only slightly ameliorated by elevated [ CO 2 ]. Variability in soil N availability among plots accounted for the spatial variability in F soil , showing a decrease of ca. 114 g C m −2 yr −1 per 1 g m −2 increase in soil N availability, with consistently higher F soil in elevated [ CO 2 ] plots ca. 127 g C per 100 ppm [ CO 2 ] over the +200 ppm enrichment. Altogether, reflecting increased belowground carbon partitioning in response to greater plant nutritional needs, the effects of elevated [ CO 2 ] and N fertilization on F soil in this stand are sustained beyond the early stages of stand development and through stabilization of annual foliage production.

Simple additive effects are rare: a quantitative review of plant biomass and soil process responses to combined manipulations of CO 2 and temperature - Wouter I. J. Dieleman; Sara Vicca; Feike A. Dijkstra; Frank Hagedorn; Mark J. Hovenden; Klaus S. Larsen; Jack A. Morgan; Astrid Volder; Claus Beier; Jeffrey S. Dukes; John King; Sebastian Leuzinger; et al. (Global Change Biology, 2012)
In recent years, increased awareness of the potential interactions between rising atmospheric CO 2 concentrations ([ CO 2 ]) and temperature has illustrated the importance of multifactorial ecosystem manipulation experiments for validating Earth System models. To address the urgent need for increased understanding of responses in multifactorial experiments, this article synthesizes how ecosystem productivity and soil processes respond to combined warming and [ CO 2 ] manipulation, and compares it with those obtained in single factor [ CO 2 ] and temperature manipulation experiments. Across all combined elevated [ CO 2 ] and warming experiments, biomass production and soil respiration were typically enhanced. Responses to the combined treatment were more similar to those in the [ CO 2 ]‐only treatment than to those in the warming‐only treatment. In contrast to warming‐only experiments, both the combined and the [ CO 2 ]‐only treatments elicited larger stimulation of fine root biomass than of aboveground biomass, consistently stimulated soil respiration, and decreased foliar nitrogen (N) concentration. Nonetheless, mineral N availability declined less in the combined treatment than in the [ CO 2 ]‐only treatment, possibly due to the warming‐induced acceleration of decomposition, implying that progressive nitrogen limitation ( PNL ) may not occur as commonly as anticipated from single factor [ CO 2 ] treatment studies. Responses of total plant biomass, especially of aboveground biomass, revealed antagonistic interactions between elevated [ CO 2 ] and warming, i.e. the response to the combined treatment was usually less‐than‐additive. This implies that productivity projections might be overestimated when models are parameterized based on single factor responses. Our results highlight the need for more (and especially more long‐term) multifactor manipulation experiments. Because single factor CO 2 responses often dominated over warming responses in the combined treatments, our results also suggest that projected responses to future global warming in Earth System models should not be parameterized using single factor warming experiments.

Greater seed production in elevated CO 2 is not accompanied by reduced seed quality in Pinus taeda L. - DANIELLE A. WAY; SHANNON L. LADEAU; HEATHER R. MCCARTHY; JAMES S. CLARK; RAM OREN; ADRIEN C. FINZI; ROBERT B. JACKSON (Global Change Biology, 2010)
For herbaceous species, elevated CO 2 often increases seed production but usually leads to decreased seed quality. However, the effects of increased atmospheric CO 2 on tree fecundity remain uncertain, despite the importance of reproduction to the composition of future forests. We determined how seed quantity and quality differed for pine trees grown for 12 years in ambient and elevated (ambient+200 μL L −1 ) CO 2 , at the Duke Forest free‐air CO 2 enrichment (FACE) site. We also compared annual reproductive effort with yearly measurements of aboveground net primary productivity (ANPP), precipitation (P), potential evapotranspiration (PET) and water availability [precipitation minus potential evapotranspiration (P−PET)] to investigate factors that may drive interannual variation in seed production. The number of mature, viable seeds doubled per unit basal area in high‐CO 2 plots from 1997 to 2008 ( P 2 effect on mean seed mass, viability, or nutrient content. Interannual variation in seed production was positively related to ANPP, with a similar percentage of ANPP diverted to reproduction across years. Seed production was negatively related to PET ( P P P =0.88). This study adds to the few findings that, unlike herbaceous crops, woody plants may benefit from future atmospheric CO 2 by producing larger numbers of seeds without suffering degraded seed quality. Differential reproductive responses between functional groups and species could facilitate woody invasions or lead to changes in forest community composition as CO 2 rises.

Role of vegetation in determining carbon sequestration along ecological succession in the southeastern United States - PAUL C. STOY; GABRIEL G. KATUL; MARIO B. S. SIQUEIRA; JEHN‐YIH JUANG; KIMBERLY A. NOVICK; HEATHER R. McCARTHY; A. CHRISTOPHER OISHI; RAM OREN (Global Change Biology, 2008)
Vegetation plays a central role in controlling terrestrial carbon (C) exchange, but quantifying its impacts on C cycling on time scales of ecological succession is hindered by a lack of long‐term observations. The net ecosystem exchange of carbon (NEE) was measured for several years in adjacent ecosystems that represent distinct phases of ecological succession in the southeastern USA. The experiment was designed to isolate the role of vegetation – apart from climate and soils – in controlling biosphere–atmosphere fluxes of CO 2 and water vapor. NEE was near zero over 5 years at an early successional old‐field ecosystem (OF). However, mean annual NEE was nearly equal, approximately −450 g C m −2 yr −1 , at an early successional planted pine forest (PP) and a late successional hardwood forest (HW) due to the sensitivity of the former to drought and ice storm damage. We hypothesize that these observations can be explained by the relationships between gross ecosystem productivity (GEP), ecosystem respiration (RE) and canopy conductance, and long‐term shifts in ecosystem physiology in response to climate to maintain near‐constant ecosystem‐level water‐use efficiency (EWUE). Data support our hypotheses, but future research should examine if GEP and RE are causally related or merely controlled by similar drivers. At successional time scales, GEP and RE observations generally followed predictions from E. P. Odum's ‘Strategy of Ecosystem Development’, with the surprising exception that the relationship between GEP and RE resulted in large NEE at the late successional HW. A practical consequence of this research suggests that plantation forestry may confer no net benefit over the conservation of mature forests for C sequestration.

Mycorrhizal and rhizomorph dynamics in a loblolly pine forest during 5 years of free‐air‐CO 2 ‐enrichment - S. G. PRITCHARD; A. E. STRAND; M. L. McCORMACK; M. A. DAVIS; R. OREN (Global Change Biology, 2008)
Soil fungi couple plant and ecosystem resource demands to pools of soil resources. Research on these organisms is needed to predict how rising atmospheric CO 2 will influence forest ecosystem processes and soil carbon (C) sequestration potential. We examined the influence of free‐air‐CO 2 ‐enrichment (FACE) on mycorrhizal and extraradical rhizomorph dynamics over a 5‐year period in a loblolly pine forest using minirhizotrons. Standing crop of mycorrhizal root tips varied greatly spatially and through time. Summed across all years, CO 2 enrichment increased mycorrhizal root tip production by 194% in deep soil (15–30 cm) but did not influence mycorrhizal production in shallow soil (0–15 cm). Production and mortality of soil rhizomorph length was 27% and 25% greater in CO 2 ‐enriched plots compared with controls over a 5‐year period beginning in January of 2000 and running through autumn 2004. Effects of atmospheric CO 2 enrichment on longevity of mycorrhizal root tips and rhizomorphs varied with soil depth (mycorrhizae and rhizomorphs) and with diameter (rhizomorphs). For instance, survival of mycorrhizal tips was reduced in CO 2 ‐enriched plots in deep soil (15–30 cm depth) but was increased in shallower soil (0–15 cm). Rhizomorph turnover was accelerated in shallow soil but effects on survivorship in deep soil varied according to diameter. A drought in 2002 coupled with loss of leaf area to an ice storm late in 2002 were followed by reductions in rhizomorph and mycorrhizal production, increases in mortality, and decreases in standing crop during 2003 and 2004. These effects tended to be more severe in CO 2 ‐enriched plots. Positive effects of atmospheric CO 2 enrichment on mycorrhizal fungi, primarily observed in deeper soil, are probably contributing to the prolonged stimulation of NPP by CO 2 enrichment at the Duke FACE study site.

Temporal dynamics and spatial variability in the enhancement of canopy leaf area under elevated atmospheric CO 2 - HEATHER R. McCARTHY; RAM OREN; ADRIEN C. FINZI; DAVID S. ELLSWORTH; HYUN‐SEOK KIM; KURT H. JOHNSEN; BONNIE MILLAR (Global Change Biology, 2007)
Increased canopy leaf area ( L ) may lead to higher forest productivity and alter processes such as species dynamics and ecosystem mass and energy fluxes. Few CO 2 enrichment studies have been conducted in closed canopy forests and none have shown a sustained enhancement of L . We reconstructed 8 years (1996–2003) of L at Duke's Free Air CO 2 Enrichment experiment to determine the effects of elevated atmospheric CO 2 concentration ([CO 2 ]) on L before and after canopy closure in a pine forest with a hardwood component, focusing on interactions with temporal variation in water availability and spatial variation in nitrogen (N) supply. The dynamics of L were reconstructed using data on leaf litterfall mass and specific leaf area for hardwoods, and needle litterfall mass and specific leaf area combined with needle elongation rates, and fascicle and shoot counts for pines. The dynamics of pine L production and senescence were unaffected by elevated [CO 2 ], although L senescence for hardwoods was slowed. Elevated [CO 2 ] enhanced pine L and the total canopy L (combined pine and hardwood species; P L and its response to elevated [CO 2 ] was not random. Each year pine L under ambient and elevated [CO 2 ] was spatially correlated to the variability in site nitrogen availability (e.g. r 2 =0.94 and 0.87 in 2001, when L was highest before declining due to droughts and storms), with the [CO 2 ]‐induced enhancement increasing with N ( P =0.061). Incorporating data on N beyond the range of native fertility, achieved through N fertilization, indicated that pine L had reached the site maximum under elevated [CO 2 ] where native N was highest. Thus closed canopy pine forests may be able to increase leaf area under elevated [CO 2 ] in moderate fertility sites, but are unable to respond to [CO 2 ] in both infertile sites (insufficient resources) and sites having high levels of fertility (maximum utilization of resources). The total canopy L , representing the combined L of pine and hardwood species, was constant across the N gradient under both ambient and elevated [CO 2 ], generating a constant enhancement of canopy L . Thus, in mixed species stands, L of canopy hardwoods which developed on lower fertility sites (∼3 g N inputs m −2 yr −1 ) may be sufficiently enhanced under elevated [CO 2 ] to compensate for the lack of response in pine L , and generate an appreciable response of total canopy L (∼14%).

Selective enrichment, isolation and molecular detection of Salinibacter and related extremely halophilic Bacteria from hypersaline environments - Rahel Elevi Bardavid; Danny Ionescu; Aharon Oren; Fred A. Rainey; Becky J. Hollen; Danielle R. Bagaley; Alanna M. Small; Christopher McKay (Hydrobiologia, 2007)

Who Needs to Spend Money on Conservation Science Anyway? - Jonathan V. Higgins; Jerome L. Touval; Robert S. Unnasch; Steffen Reichle; David C. Oren; William R. Waldman; Jonathan M. Hoekstra (Conservation Biology, 2006)

Separating the effects of climate and vegetation on evapotranspiration along a successional chronosequence in the southeastern US - PAUL C. STOY; GABRIEL G. KATUL; MARIO B. S. SIQUEIRA; JEHN‐YIH JUANG; KIMBERLY A. NOVICK; HEATHER R. McCARTHY; A. CHRISTOPHER OISHI; JOSHUA M. UEBELHERR; HYUN‐SEOK KIM; RAM OREN (Global Change Biology, 2006)
We combined Eddy‐covariance measurements with a linear perturbation analysis to isolate the relative contribution of physical and biological drivers on evapotranspiration (ET) in three ecosystems representing two end‐members and an intermediate stage of a successional gradient in the southeastern US (SE). The study ecosystems, an abandoned agricultural field [old field (OF)], an early successional planted pine forest (PP), and a late‐successional hardwood forest (HW), exhibited differential sensitivity to the wide range of climatic and hydrologic conditions encountered over the 4‐year measurement period, which included mild and severe droughts and an ice storm. ET and modeled transpiration differed by as much as 190 and 270 mm yr −1 , respectively, between years for a given ecosystem. Soil water supply, rather than atmospheric demand, was the principal external driver of interannual ET differences. ET at OF was sensitive to climatic variability, and results showed that decreased leaf area index ( L ) under mild and severe drought conditions reduced growing season (GS) ET (ET GS ) by ca. 80 mm compared with a year with normal precipitation. Under wet conditions, higher intrinsic stomatal conductance ( g s ) increased ET GS by 50 mm. ET at PP was generally larger than the other ecosystems and was highly sensitive to climate; a 50 mm decrease in ET GS due to the loss of L from an ice storm equaled the increase in ET from high precipitation during a wet year. In contrast, ET at HW was relatively insensitive to climatic variability. Results suggest that recent management trends toward increasing the land‐cover area of PP‐type ecosystems in the SE may increase the sensitivity of ET to climatic variability.

Multiscale model intercomparisons of CO 2 and H 2 O exchange rates in a maturing southeastern US pine forest - M. B. SIQUEIRA; G. G. KATUL; D. A. SAMPSON; P. C. STOY; J.‐Y. JUANG; H. R. MCCARTHY; R. OREN (Global Change Biology, 2006)
We compared four existing process‐based stand‐level models of varying complexity (physiological principles in predicting growth, photosynthesis and evapotranspiration, biogeochemical cycles, and stand to ecosystem carbon and evapotranspiration simulator) and a new nested model with 4 years of eddy‐covariance‐measured water vapor ( LE ) and CO 2 ( Fc ) fluxes at a maturing loblolly pine forest. The nested model resolves the ‘fast’ CO 2 and H 2 O exchange processes using canopy turbulence theories and radiative transfer principles whereas slowly evolving processes were resolved using standard carbon allocation methods modified to improve leaf phenology. This model captured most of the intraannual variations in leaf area index ( LAI ), net ecosystem exchange ( NEE ), and LE for this stand in which maximum LAI was not at a steady state. The model comparisons suggest strong linkages between carbon production and LAI variability, especially at seasonal time scales. This linkage necessitates the use of multilayer models to reproduce the seasonal dynamics of LAI , NEE , and LE . However, our findings suggest that increasing model complexity, often justified for resolving faster processes, does not necessarily translate into improved predictive skills at all time scales. Additionally, none of the models tested here adequately captured drought effects on water and CO 2 fluxes. Furthermore, the good performance of some models in capturing flux variability on interannual time scales appears to stem from erroneous LAI dynamics and from sensitivity to droughts that injects unrealistic flux variability at longer time scales.

Estimating the uncertainty in annual net ecosystem carbon exchange: spatial variation in turbulent fluxes and sampling errors in eddy‐covariance measurements - RAM OREN; CHENG‐I HSIEH; PAUL STOY; JOHN ALBERTSON; HEATHER R MCCARTHY; PETER HARRELL; GABRIEL G KATUL (Global Change Biology, 2006)
Above forest canopies, eddy covariance (EC) measurements of mass (CO 2 , H 2 O vapor) and energy exchange, assumed to represent ecosystem fluxes, are commonly made at one point in the roughness sublayer (RSL). A spatial variability experiment, in which EC measurements were made from six towers within the RSL in a uniform pine plantation, quantified large and dynamic spatial variation in fluxes. The spatial coefficient of variation (CV) of the scalar fluxes decreased with increasing integration time, stabilizing at a minimum that was independent of further lengthening the averaging period (hereafter a ‘stable minimum’). For all three fluxes, the stable minimum (CV=9–11%) was reached at averaging times ( τ p ) of 6–7 h during daytime, but higher stable minima (CV=46–158%) were reached at longer τ p (>12 h) during nighttime. To the extent that decreasing CV of EC fluxes reflects reduction in micrometeorological sampling errors, half of the observed variability at τ p =30 min is attributed to sampling errors. The remaining half (indicated by the stable minimum CV) is attributed to underlying variability in ecosystem structural properties, as determined by leaf area index, and perhaps associated ecosystem activity attributes. We further assessed the spatial variability estimates in the context of uncertainty in annual net ecosystem exchange (NEE). First, we adjusted annual NEE values obtained at our long‐term observation tower to account for the difference between this tower and the mean of all towers from this experiment; this increased NEE by up to 55 g C m −2 yr −1 . Second, we combined uncertainty from gap filling and instrument error with uncertainty because of spatial variability, producing an estimate of variability in annual NEE ranging from 79 to 127 g C m −2 yr −1 . This analysis demonstrated that even in such a uniform pine plantation, in some years spatial variability can contribute ∼50% of the uncertainty in annual NEE estimates.

An outbreak of Q fever in an urban area in Israel - I. Oren; Z. Kraoz; Y. Hadani; I. Kassis; N. Zaltzman-Bershadsky; R. Finkelstein (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Contrasting responses to drought of forest floor CO 2 efflux in a Loblolly pine plantation and a nearby Oak‐Hickory forest - S. Palmroth; C. A. Maier; H. R. McCarthy; A. C. Oishi; H.‐S. Kim; K.H. Johnsen; G. G. Katul; R. Oren (Global Change Biology, 2005)
Forest floor CO 2 efflux ( F ff ) depends on vegetation type, climate, and soil physical properties. We assessed the effects of biological factors on F ff by comparing a maturing pine plantation (PP) and a nearby mature Oak‐Hickory‐type hardwood forest (HW). F ff was measured continuously with soil chambers connected to an IRGA during 2001–2002. At both sites, F ff depended on soil temperature at 5 cm ( T 5 ) when soil was moist (soil moisture, θ >0.20 m 3 m −3 ), and on both T 5 and θ when soil was drier. A model ( F ff ( T 5 , θ )) explained 92% of the variation in the daily mean F ff at both sites. Higher radiation reaching the ground during the leafless period, and a thinner litter layer because of faster decomposition, probably caused higher soil temperature at HW compared with PP. The annual F ff was estimated at 1330 and 1464 g C m −2 yr −1 for a year with mild drought (2001) at PP and HW, respectively, and 1231 and 1557 g C m −2 yr −1 for a year with severe drought (2002). In the wetter year, higher soil temperature and moisture at HW compared with PP compensated for the negative effect on F ff of the response to these variables resulting in similar annual F ff at both stands. In the drier year, however, the response to soil temperature and moisture was more similar at the two stands causing the difference in the state variables to impel a higher F ff at HW. A simple mass balance indicated that in the wetter year, C in the litter–soil system was at steady state at HW, and was accruing at PP. However, HW was probably losing C from the mineral soil during the severe drought year of 2002, while PP was accumulating C at a lower rate because of a loss of C from the litter layer. Such contrasting behavior of two forest types in close proximity might frustrate attempts to estimate regional carbon (C) fluxes and net C exchange.

Carbon dioxide and water vapor exchange in a warm temperate grassland - K. A. Novick; P. C. Stoy; G. G. Katul; D. S. Ellsworth; M. B. S. Siqueira; J. Juang; R. Oren (Oecologia, 2004)

Exposure to an enriched CO 2 atmosphere alters carbon assimilation and allocation in a pine forest ecosystem - Karina V. R. Schäfer; Ram Oren; David S. Ellsworth; Chun‐Ta Lai; Jeffrey D. Herrick; Adrien C. Finzi; Daniel D. Richter; Gabriel G. Katul (Global Change Biology, 2003)
We linked a leaf‐level CO 2 assimilation model with a model that accounts for light attenuation in the canopy and measurements of sap‐flux‐based canopy conductance into a new canopy conductance‐constrained carbon assimilation (4C‐A) model. We estimated canopy CO 2 uptake ( A nC ) at the Duke Forest free‐air CO 2 enrichment (FACE) study. Rates of A nC estimated from the 4C‐A model agreed well with leaf gas exchange measurements ( A net ) in both CO 2 treatments. Under ambient conditions, monthly sums of net CO 2 uptake by the canopy ( A nC ) were 13% higher than estimates based on eddy‐covariance and chamber measurements. Annual estimates of A nC were only 3% higher than carbon (C) accumulations and losses estimated from ground‐based measurements for the entire stand. The C budget for the Pinus taeda component was well constrained (within 1% of ground‐based measurements). Although the closure of the C budget for the broadleaf species was poorer (within 20%), these species are a minor component of the forest. Under elevated CO 2 , the C used annually for growth, turnover, and respiration balanced only 80% of the A nC . Of the extra 700 g C m −2 a −1 (1999 and 2000 average), 86% is attributable to surface soil CO 2 efflux. This suggests that the production and turnover of fine roots was underestimated or that mycorrhizae and rhizodeposition became an increasingly important component of the C balance. Under elevated CO 2 , net ecosystem production increased by 272 g C m −2 a −1 : 44% greater than under ambient CO 2 . The majority (87%) of this C was sequestered in a moderately long‐term C pool in wood, with the remainder in the forest floor–soil subsystem.

Reduction of forest floor respiration by fertilization on both carbon dioxide‐enriched and reference 17‐year‐old loblolly pine stands - JOHN R. BUTNOR; KURT H. JOHNSEN; RAM OREN; GABRIEL G. KATUL (Global Change Biology, 2003)
Elevated atmospheric carbon dioxide (CO 2 e ) increases soil respiration rates in forest, grassland, agricultural and wetland systems as a result of increased growth, root biomass and enhanced biological activity of soil microorganisms. Less is known about how forest floor fluxes respond to the combined effects of elevated CO 2 and nutrient amendments; until now no experiments have been in place with large forest trees to allow even preliminary investigations. We investigated changes in forest floor respiration (S ff ) in a Pinus taeda L. plantation fumigated with CO 2 by using free‐air CO 2 enrichment (FACE) technology and given nutrient amendments. The prototype FACE apparatus (FACEp; 707 m 2 ) was constructed in 1993, 10 years after planting, on a moderate fertility site in Duke Forest, North Carolina, USA, enriching the stand to 55 Pa (CO 2 e ). A nearby ambient CO 2 (CO 2 a ) plot (117 m 2 ) was designated at the inception of the study as a reference (Ref). Both FACEp and Ref plot were divided in half and urea fertilizer was applied to one half at an annual rate of 11.2 g N m −2 in the spring of 1998, 1999 and 2000. Forest floor respiration was monitored continuously for 220 days – March through November 2000 – by using two Automated Carbon Efflux Systems. Thirty locations (491 cm 2 each) were sampled in both FACEp and Ref, about half in each fertility treatment. Forest floor respiration was strongly correlated with soil temperature at 5 cm. Rates of S ff were greater in CO 2 e relative to CO 2 a (an enhancement of ∼178 g C m −2 ) during the measurement period. Application of fertilizer resulted in a statistically significant depression of respiration rates in both the CO 2 a and CO 2 e plots (a reduction of ∼186 g C m −2 ). The results suggest that closed canopy forests on moderate fertility sites cycle back to the atmosphere more assimilated carbon (C) than similar forests on sites of high fertility. We recognize the limitations of this non‐replicated study, but its clear results offer strong testable hypotheses for future research in this important area.

Hydrologic balance in an intact temperate forest ecosystem under ambient and elevated atmospheric CO 2 concentration - Karina V. R. Schäfer; Ram Oren; Chun‐Ta Lai; Gabriel G. Katul (Global Change Biology, 2002)
Increasing atmospheric CO 2 concentration decreases stomatal conductance in many species, but the savings of water from reduced transpiration may permit the forest to retain greater leaf area index ( L ). Therefore, the net effect on water use in forest ecosystems under a higher CO 2 atmosphere is difficult to predict. The free air CO 2 enrichment (FACE) facility ( n = 3) in a 14‐m tall (in 1996) Pinus taeda L. stand was designed to reduce uncertainties in predicting such responses. Continuous measurements of precipitation, throughfall precipitation, sap flux, and soil moisture were made over 3.5 years under ambient (CO 2 a ) and elevated (CO 2 e ) ambient + 200 µmol mol −1 ). Annual stand transpiration under ambient CO 2 conditions accounted for 84–96% of latent heat flux measured with the eddy‐covariance technique above the canopy. Under CO 2 e , P. taeda transpired less per unit of leaf area only when soil drought was severe. Liquidambar styraciflua , the other major species in the forest, used progressively less water, settling at 25% reduction in sap flux density after 3.5 years under CO 2 e . Because P. taeda dominated the stand, and severe drought periods were of relatively short duration, the direct impact of CO 2 e on water savings in the stand was undetectable. Moreover, the forest used progressively more water under CO 2 e , probably because soil moisture availability progressively increased, probably owing to a reduction in soil evaporation caused by more litter buildup in the CO 2 e plots. The results suggest that, in this forest, the effect of CO 2 e on transpiration was greater indirectly through enhanced litter production than directly through reduced stomatal conductance. In forests composed of species more similar to L. styraciflua , water savings from stomatal closure may dominate the response to CO 2 e .

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Meeting Global Policy Commitments: Carbon Sequestration and Southern Pine Forests - K.H. Johnsen; D. Wear; R. Oren; R.O. Teskey; F. Sanchez; R. Will; J. Butnor; D. Markewitz; D. Richter; T. Rials; H.L. Allen; J. Seiler; et al. (Journal of Forestry, 2001)
In managed forests, the amount of carbon further sequestered will be determined by (1) the increased amount of carbon in standing biomass (resulting from land-use changes and increased productivity); (2) the amount of recalcitrant carbon remaining below ground at the end of rotations; and (3) the amount of carbon sequestered in products created from harvested wood. Because of the region's high productivity and industrial infrastructure, carbon sequestration via southern pine forests could be increased, and this may benefit the nation in terms of global policy commitments.

Sensitivity of mean canopy stomatal conductance to vapor pressure deficit in a flooded Taxodium distichum L. forest: hydraulic and non-hydraulic effects - R. Oren; J. S. Sperry; B. E. Ewers; D. E. Pataki; N. Phillips; J. P. Megonigal (Oecologia, 2001)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Abstracts of Presentations at the 19th Congress of the Israeli Phytopathological Society - M. Raviv; I. Nir; Y. Pinkas; E. Shabi; S. Elisha; Marcell Maimon; Y. Szmulewich; S. Freeman; E. Shabi; Y. Nitzani; Talma Katan; Y. Luzzati; et al. (Phytoparasitica, 1998)

Tetrahydromethanopterin-dependent serine transhydroxymethylase from Methanobacterium thermoautotrophicum - J. C. Hoyt; A. Oren; J. C. Escalante-Semerena; R. S. Wolfe (Archives of Microbiology, 1986)